The impact of clamp castration on the behaviour and body temperature of reindeer (Rangifer tarandus tarandus) – effects of local anesthesia and non-steroidal anti-inflammatory drug - Nurmi, Hanna Kristiina; Laaksonen, Sauli; Häätylä, Taija Susanna; Sauvala, Mikaela; Valros, Anna; Hänninen, Laura (Applied Animal Behaviour Science, 2023)
Yearly, 2500–4000 reindeer (Rangifer tarandus tarandus) bulls are castrated in Finland, mostly without pain alleviation. No previous research exists concerning pain-related behaviours during castration in reindeer. Our aims were to investigate the effects of Burdizzo clamp castration on reindeer behaviour and rectal temperature during the procedure, and how these are affected by handling, local anaesthesia (LA) with lidocaine, and a non-steroidal anti-inflammatory (NSAID) drug meloxicam. A total of 44 1.5-year-old-reindeer were clamp castrated with either no pain alleviation (TRAD), perioperative meloxicam (NSAID), local lidocaine anaesthesia (LA), or with a combination of LA and NSAID (LA+NSAID), n = 11 in each treatment group. The fifth group was a non-castrated control (CONTROL), n = 11. We scored the reindeer behaviours, i.e., head, neck, and leg movements, nostril closure, panting, defecation, abdominal muscle contractions, and respiratory rate, from video recordings prior to and during castration and LA injection. We measured rectal temperatures (T) during the experiment and scored the number of reindeer reaching a T of at least 39.5ºC. Differences between treatments were analysed with the Kruskal-Wallis and chi square tests and differences between sampling intervals with the Wilcoxon signed rank and Friedman tests. During castration, nostril closures and abdominal muscle contractions occurred more often and for longer duration in the TRAD, NSAID, LA, and LA+NSAID groups than in the CONTROL group (p < 0.05 for all) or prior to castration (p < 0.001 for all). T increased during the experiment for all treatments. Overall, a total of 25 animals reached T 39.5ºC and treatments differed (p < 0.05): a larger number reached T 39.5ºC in the LA+NSAID group (11/11) than in the TRAD (2/10), NSAID (3/11), LA (4/11), or CONTROL (5/11) groups. The median respiratory rates decreased overall during the experiment for all treatments. During castration, TRAD had the highest median respiratory rate, differing from ...